Sutte Indicator: A Technical Indicator in Stock Market - Ahmar, Ansari Saleh (International Journal of Economics and Financial Issues, 2017)
This study aims at development of the technical indicator in Stock Market as Sutte Indicator. Sutte Indicator in stock trading that will assist in the investment decision-making process which is to buy or sell stocks. This study took data from PT. Astra Agro Lestari Tbk. (AALI) which is listed in the Indonesia Stock Exchange (BEI) in the period of 5 April 2001 to 20 September 2016. To find out the performance of Sutte Indicator, two other technical analysis are used as a comparison, they are Simple Moving Average (SMA) and Moving Average Convergence/Divergence (MACD). The mean of square error (MSE), mean absolute deviation (MAD), and mean absolute percentage error (MAPE) are used to find out a comparison of the level of reliability in predicting the stock data. The results of this study are Sutte Indicator could be used as a reference in predicting stock movements. Sutte Indicator have a better level of reliability compared to two other indicators method SMA and MACD based on the MSE, MAD and MAPE. Keywords: Stock Market; Sutte Indicator; Technical Analysis. JEL Classifications: C58 D53